2019
DOI: 10.1016/j.celrep.2019.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside Augments the Aged Human Skeletal Muscle NAD+ Metabolome and Induces Transcriptomic and Anti-inflammatory Signatures

Abstract: Highlights d NR supplementation in aged subjects augments the skeletal muscle NAD + metabolome d NR supplementation does not affect skeletal muscle mitochondrial bioenergetics d NR supplementation reduces levels of circulating inflammatory cytokines

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
312
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(340 citation statements)
references
References 71 publications
(103 reference statements)
22
312
5
1
Order By: Relevance
“…The compiled results from the present study do not corroborate findings obtained in preclinical studies and challenge whether NAD + precursor supplementation will translate to improved mitochondrial health in human skeletal muscle. Our results align with a recently published randomized, placebo-controlled crossover study investigating the effects of NR 1 g/day for 21 days in 12 aged (70-80 years) males (Elhassan et al 2019). In this study, NR did not augment NAD + levels in skeletal muscle, although nicotinic acid adenine dinucleotide (NAAD) as well as NAM degradative products increased upon NR supplementation, suggesting oral bioavailability of NR to skeletal muscle.…”
Section: Figure 7 Hierarchical Clustering Analysis On the Subset Ofsupporting
confidence: 91%
See 2 more Smart Citations
“…The compiled results from the present study do not corroborate findings obtained in preclinical studies and challenge whether NAD + precursor supplementation will translate to improved mitochondrial health in human skeletal muscle. Our results align with a recently published randomized, placebo-controlled crossover study investigating the effects of NR 1 g/day for 21 days in 12 aged (70-80 years) males (Elhassan et al 2019). In this study, NR did not augment NAD + levels in skeletal muscle, although nicotinic acid adenine dinucleotide (NAAD) as well as NAM degradative products increased upon NR supplementation, suggesting oral bioavailability of NR to skeletal muscle.…”
Section: Figure 7 Hierarchical Clustering Analysis On the Subset Ofsupporting
confidence: 91%
“…However, this did not confer changes in mitochondrial respiration or content (Elhassan et al . ). Although positive outcomes from clinical trials are still lacking, in vitro studies have demonstrated effects of NR on mitochondria in several human cell types.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the anti-inflammatory properties of NAD + -boosting compounds have been extended to the human scenario. The short-term administration (21 days) of NR to aged individuals increases NAD + levels in the muscle and reduces the expression of the inflammaging-associated cytokines IL-6, IL-5, and IL-2 [93]. This study opens a door for longer NR interventions in aged humans.…”
Section: Nad + Precursorsmentioning
confidence: 79%
“…Taken together, the findings collected by Dollerup and collaborators provide robust evidence that 12 weeks of NRS does not improve skeletal muscle mitochondrial respiration and whole-body glucose homeostasis in a population of obese and insulin-resistant men. In support of this conclusion, research recently published in Cell Reports shows in healthy elderly individuals that 250 mg of NRS twice a day for 21 days does not improve skeletal muscle mitochondrial bioenergetics and whole-body glucose homeostasis (Elhassan et al 2019). J Physiol 598.4 Collectively, these findings therefore challenge preclinical data obtained in animal models and indicate that NRS is ineffective in enhancing mitochondrial respiration and whole-body glucose homeostasis in obese insulin-resistant men.…”
mentioning
confidence: 95%